The Development of Project Based Learning Module for Vocational High Schools to Improve Critical Thingking Skills - Baidowi, Baidowi; Arjudin, Arjudin; Novitasari, Dwi; Kertiyani, Ni Made Intan (JTAM (Jurnal Teori dan Aplikasi Matematika), 2023)
Critical thinking is one of the skills needed by vocational high school students in the world of work and has a positive impact on students' fieldwork practices. Therefore the aim of this research is to produce a mathematics module focused on critical thinking skills using a project-based learning model. Thiagarajan's 4D development model, namely define, design, develop, and dissemination, is used in this research and development model. Validation tests, questionnaires, observations, interviews, and critical thinking tests were used to collect data. Data analysis was carried out quantitatively and qualitatively. Quantitative analysis uses descriptive statistical tests and T-tests while qualitative analysis comes from suggestions and input from media experts, materials, practitioners, teachers, and students. The results showed that: (1) the mathematics module for grade 11th vocational high school met valid criteria based on the assessment of material experts, media experts, practitioners, teachers, and students; and (2) with a sig score of 0.000 from the T-test, students who took the module these have better critical thinking skills than those who don't. So that this module can be classified as effective for use in learning. This indicates that this module meets the requirements for use in learning.